Streaming media in a different contexts : engineering and education graduation - Santos, Henrique Dinis dos (2007)
In this paper we describe a functional model that will be used to develop learning units supported by streaming media contents. The mais goal is to test this new methodology by carrying out several padagogical experiences with students and teachers from different scientifies areas, from Engineering to Education. More precisely, the target courses are Applied Mathematics, Computation Systems, Digital Control and Methods and Tchniques of Educational Administration. Steaming media isn viewed as a tool to support innovative padagogical activities, capable of addressing the new challenges introduced by the current demands of pedagogical environments. The teacher must be capable to formulate new teaching strategies to guarantee the expected learning levels and the entailment of the communication and the interativity that shoud exist inside of the classroom (...)